Prevalence of fatigue and associated factors in chronic low back pain patients Prevalencia y factores asociados con la fatiga en pacientes con dolor lumbar crónico Prevalência de fadiga e fatores relacionados em pacientes com dor lombar crônica - Marina de Góes Salvetti; Cibele Andrucioli de Mattos Pimenta; Patrícia Emília Braga; Michael McGillion (Universidade de São Paulo, 2013)
OBJECTIVES: to determine the prevalence and key factors associated with fatigue in chronic low back pain patients. METHODS: cross-sectional study of 215 chronic low back pain patients from three health care centers and two industrial corporations. The crude prevalence of fatigue and its 95% confidence interval (CI) were calculated. Associations between fatigue and the independent variables were measured. RESULTS: the prevalence of fatigue among the participants was 26.0% [95% CI: 20.3 - 32.5]. Fatigue was independently associated with depression and self-efficacy. An increase of one unit in the score of depression increased the risk of fatigue by 9%; an increase of one unit in the score of self-efficacy reduced the risk of fatigue by 2%. CONCLUSIONS: fatigue was prevalent in chronic low back pain patients and associated with depression and self-efficacy. Knowing these factors can direct strategies for prevention and control of fatigue in chronic low back pain patients. OBJETIVOS: Determinar la prevalencia y factores asociados con la fatiga en pacientes con dolor lumbar crónico. MÉTODOS: Estudio transversal con 215 pacientes con dolor lumbar crónico en tres servicios de salud y dos industrias. La prevalencia de la fatiga y su intervalo de confianza (IC) se calcularon. Las asociaciones entre variables independientes y la fatiga se calcularon. RESULTADOS: La prevalencia de la fatiga en los pacientes con dolor lumbar crónico fue del 26% [20,3 a 32,5, IC 95%]. La fatiga se asocia con la depresión y la autoeficacia. El aumento de un punto en la puntuación de depresión aumentó un 9% el riesgo de fatiga y un aumento de un punto en la auto-eficacia reduce el riesgo de la fatiga en el 2%. CONCLUSIONES: La fatiga es frecuente en pacientes con dolor lumbar crónico y se asocia con la depresión y la autoeficacia. Conocer estos factores puede dirigir las estrategias de prevención y control de la fatiga en pacientes con dolor lumbar crónico. OBJETIVOS: determinar a prevalência e os principais fatores relacionados à fadiga em pacientes com dor lombar crônica. MÉTODOS: trata-se de estudo transversal, com a participação de 215 pacientes com dor lombar crônica, em três centros de saúde e duas indústrias. Foram calculadas a prevalência bruta de fadiga e seu intervalo de confiabilidade de 95% (IC). RESULTADOS: a prevalência de fadiga entre os participantes com dor lombar crônica foi de 26% [20,3-32,5; IC 95%]. A fadiga foi associada à depressão e à autoeficácia de forma independente. O aumento de um ponto no escore de depressão aumentou o risco de fadiga em 9% e o aumento de um ponto no escore de autoeficácia reduziu o risco de fadiga em 2%. CONCLUSÕES: fadiga foi um fator predominante em pacientes com dor lombar crônica e indicou relação com depressão e autoeficácia. O conhecimento desses fatores pode orientar estratégias para prevenção e controle da fadiga em pacientes com dor lombar crônica.